Smart and sustainable city Baghdad - Waheeb, Rasha A.; Andersen, Bjorn S.; Wheib, Kusay A. (Frontiers in Sustainable Cities, 2025)
IntroductionThe Smart Sustainable City Baghdad (SSCB-App) initiative advances a novel, multi-sectoral framework for urban transformation in fragile and conflict-affected contexts. Conceived as both a technological innovation and a governance instrument, the SSCB-App operationalizes the principles of resilience, sustainability, and inclusivity within a city marked by protracted conflict, infrastructural collapse, and institutional fragmentation. Through the integration of real-time data analytics, interactive dashboards, and scenario-based simulations, the application systematically engages critical urban domains—energy, water, transportation, healthcare, education, security, environment, and governance—while linking them to the global normative architecture of the United Nations Sustainable Development Goals (SDGs).MethodsThe contribution of this study is threefold. First, it redefines post-conflict urban recovery by embedding resilience thinking into practical decision-support systems that allow policymakers to anticipate risks, test alternative strategies, and align reconstruction efforts with long-term sustainability objectives. Second, it demonstrates how digital technologies, when strategically integrated with governance frameworks, can mediate the tension between immediate stabilization needs and structural reforms aimed at equity and accountability.ResultsThird, by situating Baghdad as a paradigmatic case, the SSCB-App underscores the epistemic value of fragile cities as laboratories of innovation, where the intersections of conflict, governance, and sustainability illuminate broader theoretical debates in urban studies and development research. Ultimately, the SSCB-App transcends conventional reconstruction by articulating a transferable model that is at once context-specific and globally relevant.DiscussionIt positions Baghdad not merely as a site of recovery but as a reference point for reimagining the role of smart technologies in enabling resilient, just, and sustainable urban futures. This analytical and model-based study provides an integrated framework for transforming Baghdad into a smart and sustainable city by combining urban planning, renewable energy, environmental protection, and intelligent governance systems.